2011
DOI: 10.1007/s00167-010-1355-2
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus non-operative management of patellar dislocation. A meta-analysis

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
103
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 49 publications
1
103
1
2
Order By: Relevance
“…According to a recent meta-analysis, operative treatment is associated with a higher risk of patellofemoral osteoarthritis [16]. The authors concluded that a delay of surgical intervention, allowing recurrent dislocations to cause further chondral damage, might be responsible for the high risk of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent meta-analysis, operative treatment is associated with a higher risk of patellofemoral osteoarthritis [16]. The authors concluded that a delay of surgical intervention, allowing recurrent dislocations to cause further chondral damage, might be responsible for the high risk of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that operatively treated knees are associated with a lower risk of recurrent dislocations, they may bear a higher risk of subsequent patellofemoral joint degeneration [15,16]. Late osteoarthritis is therefore considered to be an impending risk of this surgical technique due to increased patellofemoral contact pressure and changes of knee joint loading [17][18][19].…”
mentioning
confidence: 99%
“…Recurrent patellar dislocation can be caused by both bony and soft tissue abnormalities as highlighted in the abstract [1,2]. It has recently been shown that MCL injuries can co-exist following patellar dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical management in all trials differed and consisted of initial immobilization in a cast or splint for a variable duration of time followed by active mobilization with variable physiotherapy regimens. There is considerable disagreement about the best nonoperative treatment approaches, and further research into identification of an ideal nonoperative management strategy has been previously recommended [8].…”
Section: Upon Closer Inspectionmentioning
confidence: 99%
“…Most techniques generally included repair or reconstruction of the soft tissue structures in the medial aspect of the knee, but specific techniques included MPFL suture repair, medial soft-tissue reefing with MPFL augmentation, combinations with lateral release, and MPFL reconstruction. Another systematic review addressing this topic found that the rationale for undertaking particular techniques rarely were reported despite considerable variability in surgical technique across studies in that review [8]. Additionally, anatomic considerations and diagnostic evaluation of associated conditions such as trochlear hypoplasia or generalized soft-tissue laxity were unreported, which prevents assessment of optimal techniques in specific patient populations.…”
Section: Upon Closer Inspectionmentioning
confidence: 99%